2014
DOI: 10.4184/asj.2014.8.6.768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spinous Process-Splitting Laminectomy versus Conventional Laminectomy for Lumbar Spinal Stenosis

Abstract: Study DesignSeventy-five patients who had been treated for lumbar spinal stenosis (LSS) were reviewed retrospectively.PurposeInvasion into the paravertebral muscle can cause major problems after laminectomy for LSS. To address these problems, we performed spinous process-splitting laminectomy. We present a comparative study of decompression of LSS using 2 approaches.Overview of LiteratureThere are no other study has investigated the lumbar spinal instability after spinous process-splitting laminectomy.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…We do not have long-term follow-up information, but the results reported in the literature have been very favorable and stimulated the introduction of this technique into our field of activity. 2,3,7,8 The efficacy of the surgical treatment of lumbar canal stenosis has been well-evidenced in prospective, randomized studies 9,10 and it has been established that decompression of the vertebral canal, lateral recess, and vertebral foramen promote the improvement of symptoms. However, there are potential risks arising from the conventional surgical procedure involving open dissection with displacement and retraction of the paravertebral muscles, resection of the vertebral lamina, facet joints, spinous process, and injury to the posterior ligament structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We do not have long-term follow-up information, but the results reported in the literature have been very favorable and stimulated the introduction of this technique into our field of activity. 2,3,7,8 The efficacy of the surgical treatment of lumbar canal stenosis has been well-evidenced in prospective, randomized studies 9,10 and it has been established that decompression of the vertebral canal, lateral recess, and vertebral foramen promote the improvement of symptoms. However, there are potential risks arising from the conventional surgical procedure involving open dissection with displacement and retraction of the paravertebral muscles, resection of the vertebral lamina, facet joints, spinous process, and injury to the posterior ligament structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of case series with long follow-up periods have shown lower rates of vertebral segment instability with the spinous process splitting technique. 2 The clinical parameters chosen for the preliminary evaluation of the group of patients studied were lumbar and lower limb pain, considering that these symptoms may be presented in different types of lumbar stenosis (central, lateral recess, or foraminal). 9 The use of specific questionnaires might better assess the function of operated patients, but because of the short evaluation period only lumbar and lower limb pain were selected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less invasive spinal procedures have come into wide use, and previous studies have found that less invasive surgeries have equal or superior outcomes compared to conventional open surgery [1][2][3][4][5][6][7][8]. The purpose of this retrospective case-control study was to determine whether the differences among 3 paraspinous unilateral approaches for lumbar decompression would suggest that less invasive procedures would have superior outcomes compared to conventional procedures for at least 2 years.…”
Section: Introductionmentioning
confidence: 99%